2003
DOI: 10.1097/00129492-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cements as Adjuvant Techniques for Ossicular Chain Reconstruction

Abstract: Hydroxyapatite and Dahllite bone cements showed evidence of osseointegration with ossicular bone in the guinea pig model. Further studies are under way to determine the osseointegrative capacity of Dahllite cement between the guinea pig malleus and a partial prosthesis, and any ototoxic effects with use in the middle ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 10 publications
0
32
0
4
Order By: Relevance
“…PORPs and total ossicular replacement prostheses (TORPs) have the advantage of being readily available, but extrusion and stability problems (with or without displacement) are deWnite disadvantages, particularly in unstable or not well-aerated middle ears. In patients requiring revision PORP/TORP ossiculoplasty, half of the failures are indeed due to prosthesis displacement [1,7]. The risk of extrusions is much higher in inXamed and atelectatic ears [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…PORPs and total ossicular replacement prostheses (TORPs) have the advantage of being readily available, but extrusion and stability problems (with or without displacement) are deWnite disadvantages, particularly in unstable or not well-aerated middle ears. In patients requiring revision PORP/TORP ossiculoplasty, half of the failures are indeed due to prosthesis displacement [1,7]. The risk of extrusions is much higher in inXamed and atelectatic ears [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Dost et al found new bone formation surrounding Bioverit Õ I þ II, hydroxyapatite and Ceravital Õ implants, and also in contact with the middle ear wall in guinea pigs [18,19,23]. Additionally, a significant amount of new bone around the ossicle was observed in a reconstruction with hydroxyapatite cement and dahllite cement [24]. This fact leads to the conclusion that the extensive ossification limits the use of guinea pigs for research about ossicular chain replacements [18].…”
Section: Animal Modelmentioning
confidence: 99%
“…Subsequently, in half of the patients requiring revision ossiculoplasty due to poor hearing results, prosthesis displacement is the cause for failure. Other reasons are extrusion and absorption of the biomaterial [6].…”
Section: Indications For Ossicular Chain Reconstructionmentioning
confidence: 99%
“…Reports on successful implantation in unsterile sites like the paranasal sinuses for sinus lift in dentistry and sinus obliteration in rhinology [25,26] makes the use for ossicular chain reconstruction considerable. Recent in vivo animal studies showed evidence of osseointegration with ossicular bone [6].…”
Section: Hydroxyapatitementioning
confidence: 99%